2017
DOI: 10.1155/2017/2505034
|View full text |Cite
|
Sign up to set email alerts
|

Application of Pneumatic Lithotripter and Holmium Laser in the Treatment of Ureteral Stones and Kidney Stones in Children

Abstract: Objective. Treatment options for urolithiasis in children include URSL and RIRS. Various types of energy are used in the disintegration of deposits in these procedures. We decided to evaluate the usefulness of URSL and RIRS techniques and compare the effectiveness of pneumatic lithotripters and holmium lasers in the child population based on our experience. Materials and Methods. One hundred eight (108) children who underwent URSL and RIRS procedures were enrolled in the study and divided into two (2) groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
5
0
6
Order By: Relevance
“…Another study by Linjin et al 17 also confirmed less operating time with LL (28 ± 9.2 vs 41 ± 12.4, p 0.001) as suggested by our study. Zyczkowski M et al 18 studied 108 children and found statistically significant shorter MOT in LL group (34 vs 56 minutes, p 0.04).…”
Section: Discussionmentioning
confidence: 94%
“…Another study by Linjin et al 17 also confirmed less operating time with LL (28 ± 9.2 vs 41 ± 12.4, p 0.001) as suggested by our study. Zyczkowski M et al 18 studied 108 children and found statistically significant shorter MOT in LL group (34 vs 56 minutes, p 0.04).…”
Section: Discussionmentioning
confidence: 94%
“…19 In another study about the application of both of these technologies in renal and ureteral stones in pediatric age groups, Marcin et al concluded that Ho: YAG laser reduced the operation time and increased the efficacy of treatment, especially in renal calculi in comparison to LL. 20 Yin et al in their meta-analysis found that Ho: YAG LL had significant superiority in comparison to PL in terms of early stone-free rate, delayed stone-free rate, shorter operative time and lower stone migration rate, but not yet in the postoperative hematuria rate and the ureteral perforation rate. 4 They did not have any comparison between the costs of these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of lithotripter activation differs in almost every referenced research; the reason could be the composition and size of the targeting stone 24 . Another study indicated lower operative duration and higher clearance rates in the holmium YAG laser group as compared to pneumatic 25 . Although the safety profile of Ho YAG: Laser is improved as compared to pneumatic lithotripter, the choice of using this modality is still doubtful for proximal ureteric stones.…”
Section: Resultsmentioning
confidence: 96%